The performance of international organizations: a policy output approach. Issue 7 (8th August 2016) - Tallberg, Jonas; Sommerer, Thomas; Squatrito, Theresa; Lundgren, Magnus
ABSTRACT: Many problems confronting today's societies are transnational in character, leading states to increasingly rely on international organizations (IOs) for policy solutions. Yet, the performance of IOs varies extensively. This contribution suggests that systematic, comparative research is required to advance our understanding of IO performance, and that a policy output approach offers particular advantages for that purpose. This approach privileges the results IOs produce in terms of policies, and is distinct from the main alternative approaches to IO performance, emphasizing either behavioural change by targets (policy outcome) or problem-solving effectiveness (policy impact). The contribution introduces a typology that captures five generic features of policy – volume, orientation, type, instrument and target – and explains how these dimensions may be used to map the output and assess the performance of IOs. The contribution concludes by discussing what methods and theories may be most useful in explaining policy output, as the research agenda on IO performance advances.